Fluktuasi harga sahama perusahaan sub-sektor restoran, hotel dan pariwisata sebelum dan setelah pandemi COVID-19 - Veny Veny; Ellyanna Junita; Maria Fransisca (LPMP Imperium, 2022)
This study was conducted to see whether there is a similar influence on fundamental factors such as net profit margin, debt to assets ratio, and firm size on share prices of companies in the restaurant, hotel, and tourism sub-sector in the pre-pandemic period after the covid-19 pandemic. The research method used in this study is panel data regression to see the relationship between net profit margin, debt to assets ratio, firm size, and stock prices before and after the covid-19 pandemic. The research method in this study is the model suitability test, with the Chow test, Hausman test, and LM test. The test will continue with panel data regression. The sampling method is a purposive sampling method. The results of this study state that the variables of net profit margin and firm size have a significant negative effect on the stock prices of the restaurant, hotel, and tourism sub-sectors before and after the covid-19 pandemic. The variable debt to assets ratio has a positive and significant effect on stock prices of the restaurant, hotel, and tourism sub-sector before the covid-19 pandemic but has a negative and significant impact on the stock price of the restaurant, hotel, and tourism sub-sector after the covid-19 pandemic.